2012
DOI: 10.1111/j.1537-2995.2012.03902.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody levels correlate with detection of Trypanosoma cruzi DNA by sensitive polymerase chain reaction assays in seropositive blood donors and possible resolution of infection over time

Abstract: Background The clinical significance of anti-T. cruzi low-level reactive samples is incompletely understood. PCR-positive rates and antibody levels among seropositive blood donors in three countries are described. Methods Follow-up whole blood and plasma samples were collected from T. cruzi-seropositive donors from 2008-2010 in the US (n=195) and Honduras (n=58). Also 143 samples from Brazil in 1996-2002, originally positive by three serological assays, were available and paired with contemporary follow-up s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 27 publications
2
46
0
2
Order By: Relevance
“…Aliquots were frozen in Brazil at −20°C until shipped to the US REDS-II Central Laboratory (BSRI) on dry ice, followed by maintenance at −70°C. The target-capture (TC) T. cruzi real-time (RT) PCR assay used in this study [18] was developed based on the PCR method described by Virreira M et al[19] targeting kinetoplast minicircle T. cruzi DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots were frozen in Brazil at −20°C until shipped to the US REDS-II Central Laboratory (BSRI) on dry ice, followed by maintenance at −70°C. The target-capture (TC) T. cruzi real-time (RT) PCR assay used in this study [18] was developed based on the PCR method described by Virreira M et al[19] targeting kinetoplast minicircle T. cruzi DNA.…”
Section: Methodsmentioning
confidence: 99%
“…All donors reactive to both assays at the time of donation and counseling were considered eligible for this study. Follow-up samples from all enrolled subjects were retested for T. cruzi antibody under code at the REDS-II Central Laboratory in the US using an FDA-approved assay manufactured by Ortho Diagnostics [21]. All 483 control donors tested negative on their follow-up samples collected at the time of enrollment and clinical assessments for this study.…”
Section: Methodsmentioning
confidence: 99%
“…All 483 control donors tested negative on their follow-up samples collected at the time of enrollment and clinical assessments for this study. Of the 499 case donors who originally screened as seropositive at the time donation in 1998–2002, serum collected in 2008–2010 from 498 tested repeat reactive, while the samples from one donor tested just below the assay cutoff consistent with slowly progressive seroreversion [21].…”
Section: Methodsmentioning
confidence: 99%
“…cruzi parasite diversity, the possibility of patients being infected with a mixed population and a lack of data showing that parasitaemia is representative of tissue parasitism are also problematic. An additional issue with PCR is that not all Chagas patients will be PCR positive; indeed, a study showed that depending on the region, between 20% and 60% of Chagas patients are PCR negative [44].…”
Section: How Do We Clinically Assess the Efficacy Of A Chagas Drug?mentioning
confidence: 99%